(untitled) (Revista LIDER, 2020)
Territorial development is conceived as a localized process of sustainable social change whose ultimate goal is the continued progress of the territory, locality and community; these and other necessary aspects for territorial development are analyzed in this work in order to calculate the Compared Territorial Human Development (CTHDI) for all territories that make up the country and then analyze this rate similarly, but excluding the province of Havana City as the capital of the Republic of Cuba, with the aim of alleviating the statistical deviations of the index, since it has been verified that this is a more rational and equitable comparison of human development levels in the territories. This paper identifies territories with low, medium and high development. This IDHTC was determined from six indicators that have direct impact on human development. For the calculation of IDHTC unlike other indices, calculated at the national and international level, here each year analyzed and the data used covers an uninterrupted 25-year period and represents the third stage of territorial development in Cuba from 1985 to 2009, and the results of this index were validated with statistical tests, which are explained in this research.